Between-sessions reliability and magnitude differences in the isometric midthigh pull: effects of procedural and analytical variations - Stevens, L. J.; Carey, D. L.; Gastin, P. B.; James, L. P. (International Journal of Sports Physiology and Performance, 2025)
Purpose: The aim of this study was to examine the effects of procedure, ranking method, and summarization method on between-sessions reliability and magnitude of force measures for the isometric midthigh pull.